Heat and Helium-3 Fluxes from Teide Volcano, Canary Islands, Spain - Mar Alonso; Eleazar Padrón; Hirochika Sumino; Pedro A. Hernández; Gladys V. Melián; María Asensio-Ramos; Fátima Rodríguez; Germán Padilla; Marta García-Merino; Cecilia Amonte; Nemesio M. Pérez (Geofluids)
During July 2016, the first integrated heat flow, CO2, and 3He emission survey was conducted across 0.5 km2 of the summit cone and crater of Teide volcano, Tenerife, Canary Islands, Spain. The thermal energy released from Teide summit cone by diffuse degassing was 2.2 MW, and the heat flux calculated through Dawson’s method was 8.1 MW, difference due to the comparison of purely convective areas as the crater with diffusive areas as the flanks of the volcano. Diffuse CO2 output was 211±20 t d-1, and 3He emission was estimated to be within a range between 0.35 and 0.89 mol y-1. The obtained values of diffuse degassing and heat fluxes are close to others obtained for similar volcanic areas. The calculation of 3He/heat ratio for the first time in this volcanic system supports the presence of an important mantle source for the degassing of Teide volcano.